Austrian Haemophilia Registry - Reitter, S.; Sturn, R.; Streif, W.; Schabetsberger, T.; Wozak, F.; Male, C.; Muntean, W.; Pabinger, I. (Hämostaseologie, 2009)
The treatment of haemophilia requires continuous development of knowledge related to various aspects of diagnosis and therapy. It is, therefore, essential to collect valid and representative data, which are comparable on an international level. The Austrian Haemophilia Registry was set up by the Scientific Advisory Panel of the Austrian Haemophilia Society and by the patient organisation. For the design, it was decided to divide the registry into three sections, two concerning quality control and a third concerning scientific questions, the latter requiring written informed consent. A web-based software is used to collect data. Transfer and storage of data are secured and the server is situated in a computer center with video and access control. Data entry was initiated early 2008. Currently, only preliminary data are available. Our further focus is on continued data entry, which will further enable us to provide information concerning the characteristics of the haemophilia patient population in Austria and the actual treatment modalities used.
Keywords: Registry; haemophilia; Austria; quality control